The Wind Beneath their Wings - Kerur, Vandana (THE PRIMARY TEACHER, 2018)
Science is, generally, seen as a male bastion. Books on science are replete with names of ‘great’ men, who dared to experiment, explore and invent. However, as the adage goes — ‘Behind every successful man is a woman’, it is not often known how much and in what capacities the female family members have contributed to such inventions and discoveries. Their contributions may have been as routine as looking after the nourishment and other basic life needs of budding scientists or inventors, keeping them away from financial obligations, and above all, providing much needed moral support when the experiments did not go as planned, and society laughed at them in derision. This article, through the story of the famous Wright Brothers and their lesser known sister, Katharine, tries to acknowledge the unspoken and latent contributions and sacrifices made by female members in a family. It also attempts to bring forth the point that without Katharine’s support, the Wright Brothers would not have been able to invent the ‘Wright Flyer’ and the world would have never been able to see the age of aviation.